Communication Skills of School Heads and Work Motivation of Elementary Teachers Leading Up to Effective Job Performance - Hugo, Roderick O. (Future Science / FSH-PH Publications, 2024)
Teacher's quality and caliber greatly affect the success of any educational system. Effective communication from the school head and the teacher's motivation can lead to effective job performance, especially at the school level. This study investigated school heads' communication skills and elementary teachers' work motivation leading to effective job performance. Specifically, it aims to determine the demographic profile of elementary teachers. This study desired to ascertain the perceived level of motivation and identify which factors of school heads' communication skills and work motivation significantly affect the teachers' job performance. Lastly, it indicates the significant difference in the perception of elementary teachers according to their demographic profile. The study was conducted at Tayabas City Division, comprising thirty-two elementary schools within two districts, particularly in East and West. This research incorporated descriptive-quantitative research. The study found that most of the teacher respondents have a positive level of verbal, non-verbal, written, listening, and visual communication skills. Elementary teachers were disclosed to have an uplifting motivation for work in terms of job commitment, relationship, quality of work, workplace environment, policies and decision-making process, motivation, and contact between their school heads. The findings indicate that teacher-respondents have sufficient motivation from different aspects of the school they are teaching. Further, the findings indicate that teacher-respondents have sufficient motivation from different aspects of the school they are teaching. Hence, the findings indicate no statistically significant difference between their communication skills and work motivation in influencing their job performance when grouped according to their demographics.